$\sqrt {(3 + \sqrt 5 )} - \sqrt {(2 + \sqrt 3 )} = $

  • A

    $\sqrt {(5/2)} + \sqrt {(3/2)} $

  • B

    $\sqrt {(5/2)} - \sqrt {(3/2)} $

  • C

    $\sqrt {(5/2)} - \sqrt {(1/2)} $

  • D

    $\sqrt {(3/2)} - \sqrt {(1/2)} $

Similar Questions

જો $x = \sqrt 7 + \sqrt 3 $ અને $xy = 4,$ તો ${x^4} + {y^4}=$

સમીકરણ $\sqrt {(x + 10)} + \sqrt {(x - 2)} = 6$ નો ઉકેલ મેળવો.

જો ${x^y} = {y^x},$ તો ${(x/y)^{(x/y)}} = {x^{(x/y) - k}},$ કે જ્યાં $k = . . . . $

${{{{[4 + \sqrt {(15)} ]}^{3/2}} + {{[4 - \sqrt {(15)} ]}^{3/2}}} \over {{{[6 + \sqrt {(35)} ]}^{3/2}} - {{[6 - \sqrt {(35)} ]}^{3/2}}}} = $

$\sqrt {[12\sqrt 5 + 2\sqrt {(55)} ]} $ નું વર્ગમૂળ મેળવો.